Attention-Demanding Cognitive Tasks Worsen Postural Control in Patients With Cervical Dystonia: A Case-Control Study - Baione, Viola; Ferrazzano, Gina; Celletti, Claudia; De Rosa, Matteo; Belvisi, Daniele; Fabbrini, Giovanni; Galli, Manuela; Camerota, Filippo; Conte, Antonella (Frontiers in Neurology, 2021)
Background: Patients with cervical dystonia (CD) show impaired postural control, balance, and gait, likely due to abnormal head postures and sensorimotor disturbances. However, until now no study has investigated whether attention-demanding activity worsens postural control and balance in CD patients. Objective: To investigate whether patients with CD show cognitive-motor interference (CMI), a specific kind of dual-task interference that occurs during the simultaneous execution of a cognitive and motor task. This information may be useful to determine whether performing activities of daily living worsens postural control and balance in CD patients. Methods: We performed a pilot case-control study. Twenty-two patients affected by CD and 19 healthy controls were enrolled in order to test CMI. Each subject was evaluated during the execution of a cognitive task while postural stability was assessed through a stabilometric platform. Results: CD patients showed impaired postural control compared to healthy controls, with instability increasing with increasing cognitive task complexity. No relationships were found between stabilometric parameters and clinical characteristics of CD. Conclusions: Our hypothesis is that CMI in CD patients derives from deranged network connectivity when activated simultaneously during the performance of two tasks that interfere with each other and “compete” for the same resources within the cognitive system.